From Egyptian stone to sustainable binder: The impact of basalt powder on metakaolin geopolymer cement - Rashad, Alaa M.; El‑Nashar, M. H.; Refaie, Fatima Al Zahraa (Edelweiss Applied Science and Technology, 2025)
Metakaolin (MK) geopolymers offer a promising avenue for sustainable construction; however, the potential contribution of incorporating natural materials such as basalt powder (BP) remains underexplored. Egypt possesses abundant reserves of both kaolin and basalt, presenting a unique opportunity to develop sustainable construction materials using indigenous resources. This study investigates the feasibility and impact of partially substituting MK with locally sourced BP at incremental levels ranging from 2.5% to 25%. The research aims to comprehensively evaluate the influence of BP integration on specific attributes of MK geopolymer cement. Advanced analytical methods were employed to provide deeper insights into the dataset. The findings indicate that the addition of BP not only improves flowability and shortens setting time but also enhances mechanical strength, reduces drying shrinkage, and improves transport properties. By leveraging indigenous materials and aligning with Egypt’s sustainability goals and global carbon reduction efforts, this research contributes to the development of high-performance, resource-efficient geopolymer binders for sustainable construction.